Pengaruh Penambahan Silica Fume, Rasio Air-Semen, dan Rasio Semen-Agregat Terhadap Kekuatan Tekan Beton - Aditianto Ramelan; F.N. Sutandi; T. Indriati; A.S. Nugroho; A. Rozaq; R. Rachmantyo (Jurnal Metalurgi dan Material Indonesia, 2018)
Concrete is a popular building structures because it is relatively cheap, has a good strength, durable, and has easy raw materials. Therefore, various researches have been done to improve the quality of concrete, such as using mineral admixtures like silica fume and variations of aggregate. This research is done by making concrete sample for compressive strength test. The variations are the addition of silica fume (SF) with the composition of 10, 15, and 20% of mass of concrete, the ratio of water-cement (w/c), and the cement-aggregate ratio (c/a) with the composition of 0.6; 0.8; and 0.9 for 28 day test age. The aggregate used is silica sand. From the test results, the maximum compressive strength is 33.73 MPa from the sample with the composition of w/c = 0.4; SF = 15%, and c/ a = 0.9 which is higher than cement sample that has 20.85 MPa. Its compounds, which are identified with the XRD characterization, are Calcite, Quartz, Calcium Silicate Hydrate (CSH), Calcium Silicate, and Portlandite. There is also cement sample with silica fume (w/c = 0.4; SF = 10%) that has a compressive strength of 24.26 MPa. The compounds identified are Calcite, CSH, Calcium Silicate, Ettringite, and Portlandite. Addition of silica fume on cement can increase its compressive strength due to the occurrence of pozzolanic reaction. This is evidenced by the increase of CSH compounds and reduction of Portlandite compounds on the results of XRD characterization. The use of silica sand in the mix will increase concrete’s compressive strength because silica sand itself has greater compressive strength than the others.